Use of Superficial Cervical Plexus Block in Submandibular and Submental Space Abscess Drainage - Singh, Vivek; KC, Bijay; Giri, Ritesh; Bhagat, Prachi (Birat Journal of Health Sciences, 2020)
Introduction: Methods for lessening the sensation of pain during surgery date back to ancient times. Although general anesthesia is preferred over locoregional anesthesia in incision and drainage of space infection in neck region, it is expensive, with increased morbidity and mortality. Sometimes, anesthetist experienced in fiber optic-guided nasal intubation may be required due to reduced mouth opening. Hence, in such cases and poor risk patients, Superficial Cervical Plexus Block can be used in association with trigeminal V3 local anesthesia. Objective: To evaluate the efficacy of Superficial Cervical Plexus Block in incision and drainage of submandibular and submental space infection. Methodology: A prospective clinical study was carried out at Nobel Medical College and Teaching Hospital, Biratnagar, Nepal from June 2018 to May 2019 suffering from submandibular and submental space infection arising from odontogenic causes who required incision and drainage. Pain response was measured using Visual Analogue Scale. Result: Out of Twenty four patients sixteen were female and 8 were male. The age ranged from 16 to 82 years with a mean age of 40.5±18.53. The Visual Analogue Scale score ranged from 0 to 8 with a mean score of 1.5 ±1.87. One patient complained of unbearable pain and had to be converted into general anesthesia (4.16%). Conclusion: Superficial Cervical Plexus Block with trigeminal mandibular local anesthesia has a high success rate, low complication rate, and high patient acceptance rate. However, caution should be exercised to ensure a low complication rate.